Preparation method of slurry-method chromium-nickel co-permeation coating of liquid-phase multi-component binder

The preparation of chromium-nickel co-permeable coatings by slurry method of liquid phase multivariate composite adhesives solves the problems of poor adhesion and limited life of the coating in the prior art, and achieves efficient, wear-resistant and corrosion-resistant coating preparation.

CN119824364AActive Publication Date: 2025-04-15XIAN THERMAL POWER RES INST CO LTD +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411891676.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-15
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

In the prior art, the surface defect problem of metal powder coating film formation leads to the limitation of the corrosion resistance of the coating, poor adhesion, and limited coating life.

Method used

The chromium-nickel co-permeable coating was prepared by the slurry method of liquid phase multivariate composite adhesive, including workpiece cleaning, electrolytic activation, preheating, coating of chromium-nickel metal slurry, segmented drying and curing and rapid sintering.

Benefits of technology

It realizes the efficient preparation of chromium-nickel co-permeable coating. The coating has excellent resistance to high and low temperature corrosion and steam oxidation resistance, strong adhesion, and extends the service life of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119824364A_ABST
    Figure CN119824364A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a slurry-process chromium-nickel co-permeation coating of a liquid-phase multi-component composite binder, which comprises the following steps: cleaning a workpiece, electrolyzing, activating and preheating, coating the surface of the workpiece with a chromium-nickel metal slurry coating, then drying and curing in sections, and finally quickly sintering to obtain the slurry-process chromium-nickel co-permeation coating of the liquid-phase multi-component composite binder, the chromium-nickel metal slurry coating comprises a solid-phase component and a liquid-phase component. According to the chromium-nickel high-temperature corrosion-resistant coating permeated by the metal powder and the preparation method of the chromium-nickel high-temperature corrosion-resistant coating, the vacuum condition is not needed, the preparation process is simple, meanwhile, the chromium-nickel permeation layer is high in preparation efficiency, small in pollution, adjustable in thickness and good in wear resistance, and particularly, the chromium-nickel permeation layer has excellent high and low temperature corrosion resistance and steam oxidation resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material surface coatings, and in particular relates to a method for preparing a chromium-nickel co-penetration coating by a slurry method using a liquid phase multi-component composite binder. Background Art

[0002] At present, the most common anti-corrosion technology is the technology of infiltrating corrosion-resistant metals on the alloy surface, such as Cr, Si, Al, etc.; Cr is infiltrated to form a Cr2O3 film on the alloy surface, and the compactness of chromium oxide hinders the corrosion of the substrate by water vapor; Si is infiltrated to improve the corrosion resistance of the substrate itself, and the combination of the two improves the overall corrosion resistance. Due to the surface defects of the metal powder coating film, the corrosion resistance of the coating is limited. Due to the limitations of the coating preparation process, the adhesion of the coating is often poor, resulting in a limited coating life. Summary of the invention

[0003] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0004] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0005] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a chromium-nickel co-penetration coating by a slurry method using a liquid phase multi-component composite binder.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: comprising, cleaning the workpiece, electrolytically activating it and then preheating it, applying a chromium-nickel metal slurry coating to the surface of the workpiece, then drying and curing it in stages, and finally rapidly sintering it, wherein the chromium-nickel metal slurry coating comprises a solid phase component and a liquid phase component.

[0007] As a preferred embodiment of the preparation method of the present invention, the solid phase components include, by mass percentage, 50-80% chromium powder, 0-10% nickel powder, 2-20% iron, 0-5% aluminum powder and 0-45% lanthanum oxide.

[0008] As a preferred embodiment of the preparation method of the present invention, the liquid phase components include, by mass percentage, 10-30% Al(H2PO4)3, 5-15% water glass, 5-10% ammonium bromide, 10-30% acrylic resin, 10-30% epoxy resin and 10-30% curing agent.

[0009] As a preferred embodiment of the preparation method of the present invention, the workpiece includes but is not limited to carbon steel, austenitic stainless steel and high-temperature alloy.

[0010] As a preferred embodiment of the preparation method of the present invention, the preheating temperature is 150-220° C. and the preheating time is 30-60 min.

[0011] As a preferred embodiment of the preparation method of the present invention, the solid phase component and the liquid phase component are mixed at a solid-liquid (g:ml) ratio of 10:1 to 5.

[0012] As a preferred embodiment of the preparation method of the present invention, the solid phase component is ground at a speed of 350 to 400 r / min for a time of 6 to 24 h.

[0013] As a preferred embodiment of the preparation method of the present invention, the segmented drying and curing comprises pre-drying at 75-85°C for 5-30 min, then drying at 140-160°C for 30-60 min, and finally medium-temperature curing at 250-300°C for 30-60 min.

[0014] As a preferred embodiment of the preparation method of the present invention, the sintering temperature is 900-1150° C. and the sintering time is 5-30 min.

[0015] Another object of the present invention is to overcome the deficiencies in the prior art and provide a chromium-nickel co-penetration coating prepared by a slurry method of a liquid phase multi-component composite binder.

[0016] Beneficial effects of the present invention:

[0017] (1) The metal powder raw material described in the present invention is suitable for various metal workpieces whose surfaces need to be strengthened, including carbon steel, austenitic stainless steel, high-temperature alloy and other workpieces, and has a wide range of applications and strong practicality.

[0018] (2) The metal powder infiltrated chromium-nickel high-temperature corrosion-resistant coating and its preparation method described in the present invention do not need to be carried out under vacuum conditions, and the preparation process is simple. At the same time, the chromium-nickel infiltrated layer has high preparation efficiency, low pollution, adjustable thickness, good wear resistance, and especially excellent resistance to high and low temperature corrosion and steam oxidation.

[0019] (3) The metal powder-infiltrated chromium-nickel high-temperature corrosion-resistant coating of the present invention has a liquid phase composed of a variety of organic binders, which can comprehensively improve the adhesion of the coating and help extend the service life of the coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0021] Figure 1 This is a cross-sectional morphology of the chromium-rich high-temperature corrosion-resistant coating prepared on the surface of austenitic steel in Example 1 of the present invention.

[0022] Figure 2 This is a cross-sectional morphology of the chromium-rich high-temperature corrosion-resistant coating prepared on the surface of austenitic steel in Example 5 of the present invention. DETAILED DESCRIPTION

[0023] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0024] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0025] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0026] Unless otherwise specified, the raw materials used in the examples of the present invention are commercially available.

[0027] Example 1

[0028] 1) Pipeline surface cleaning

[0029] Use alcohol / acetone to clean the oil stains, dust, etc. on the surface of the pipeline, and use a steel brush to remove the surface oxide scale. Place the treated workpiece in the electrolytic cell with the workpiece to be treated as the anode and graphite as the cathode. 2 The electrolysis was carried out for 100 s. The electrolyte consisted of NiCl2·6H2O, HCl and NaCl.

[0030] 2) Slurry coating on pipeline surface

[0031] After preheating the pipe at 220℃ for 30 minutes, apply the slurry to a suitable thickness at one time by spraying (or brushing, etc.), and do not apply it in layers multiple times; the thickness of the coating slurry layer is 0.5mm.

[0032] The preparation method of metal powder coating raw materials is as follows: according to the mass percentage of the solid phase components, 50% of chromium powder, 10% of nickel powder, 10% of iron, 5% of aluminum powder and 25% of lanthanum oxide are weighed respectively, and the mixed metal mixed powder is ball-milled at a ball milling speed of 350r / min and a ball milling time of 8h to obtain the final solid phase components.

[0033] The liquid phase component is measured by mass percentage, and 30% Al(H2PO4)3, 15% water glass, 10% ammonium bromide, 15% acrylic resin, 10% epoxy resin and 20% curing agent are mixed and stirred to obtain the liquid phase component. The solid phase component and the liquid phase component are mixed according to the solid-liquid (g:ml) ratio of 10:2 to obtain the final metal powder coating raw material.

[0034] 3) Drying and curing

[0035] The metal pipe coated with the chromizing material was pre-dried at 60°C for 5 minutes, then dried at 100°C for 55 minutes, and finally cured at 250°C for 30 minutes.

[0036] 4) Rapid sintering

[0037] The pipeline is rapidly sintered, diffused and chromized by rapid heating, and then air-cooled to room temperature; the heating rate is set at 1000°C / min, the holding temperature is 950°C, and the holding time is 30min.

[0038] Example 2

[0039] 1) Pipeline surface cleaning

[0040] Use alcohol / acetone to clean the oil stains, dust, etc. on the surface of the pipeline, and use a steel brush to remove the surface oxide scale. Place the treated workpiece in the electrolytic cell with the workpiece to be treated as the anode and graphite as the cathode. 2 The electrolysis was carried out for 100 s. The electrolyte consisted of NiCl2·6H2O, HCl and NaCl.

[0041] 2) Slurry coating on pipeline surface

[0042] After preheating the pipe at 220℃ for 20 minutes, apply the slurry to a suitable thickness at one time by spraying (or brushing, etc.), and do not apply it in multiple layers; the thickness of the coating slurry layer is 0.5mm.

[0043] The preparation method of the metal powder coating raw material is as follows: according to the mass percentage of the solid phase components, 65% of chromium powder, 5% of nickel powder, 5% of iron, 5% of aluminum powder and 20% of lanthanum oxide are weighed respectively, and the mixed metal mixed powder is ball-milled at a ball milling speed of 400 r / min and a ball milling time of 8 h to obtain the final solid phase component.

[0044] The liquid phase component is measured by mass percentage, and 20% Al(H2PO4)3, 10% water glass, 7% ammonium bromide, 20% acrylic resin, 18% epoxy resin and 25% curing agent are mixed and stirred to obtain the liquid phase component. The solid phase component and the liquid phase component are mixed according to the solid-liquid (g:ml) ratio of 10:3 to obtain the final metal powder coating raw material.

[0045] 3) Drying and curing

[0046] The metal pipe coated with the chromizing material was pre-dried at 70°C for 5 minutes, then dried at 120°C for 55 minutes, and finally cured at 300°C for 30 minutes.

[0047] 4) Rapid sintering

[0048] The pipeline is rapidly sintered, diffused and chromized by rapid heating, and then air-cooled to room temperature; the heating rate is set to 1000°C / min, the holding temperature is 1000°C, and the holding time is 30min.

[0049] Example 3

[0050] 1) Pipeline surface cleaning

[0051] Use alcohol / acetone to clean the oil stains, dust, etc. on the surface of the pipeline, and use a steel brush to remove the surface oxide scale. Place the treated workpiece in the electrolytic cell with the workpiece to be treated as the anode and graphite as the cathode. 2 The electrolysis was carried out for 100 s. The electrolyte consisted of NiCl2·6H2O, HCl and NaCl.

[0052] 2) Slurry coating on pipeline surface

[0053] After preheating the pipeline at 200℃ for 50 minutes, apply the slurry to a suitable thickness at one time by spraying (or brushing, etc.), and do not apply it in layers multiple times; the thickness of the coating slurry layer is 1.0mm.

[0054] The preparation method of the metal powder coating raw material is as follows: according to the mass percentage of the solid phase components, 80% of chromium powder, 5% of nickel powder, 2% of iron, 3% of aluminum powder and 10% of lanthanum oxide are weighed respectively, and the mixed metal mixed powder is ball-milled at a ball milling speed of 400r / min and a ball milling time of 24h to obtain the final solid phase component.

[0055] The liquid phase component is measured by mass percentage, and 20% Al(H2PO4)3, 10% water glass, 5% ammonium bromide, 30% acrylic resin, 30% epoxy resin and 15% curing agent are mixed and stirred to obtain the liquid phase component. The solid phase component and the liquid phase component are mixed according to the solid-liquid (g:ml) ratio of 10:1 to 5 to obtain the final metal powder coating raw material.

[0056] 3) Drying and curing

[0057] The metal pipe coated with the chromizing material was pre-dried at 80°C for 10 minutes, then dried at 150°C for 30 minutes, and finally cured at 300°C for 20 minutes.

[0058] 4) Rapid sintering

[0059] The pipeline is rapidly sintered, diffused and chromized by rapid heating, and then air-cooled to room temperature; the heating rate is set to 1000°C / min, the holding temperature is 1150°C, and the holding time is 20min.

[0060] Example 4

[0061] 1) Pipeline surface cleaning

[0062] Use alcohol / acetone to clean the oil stains, dust, etc. on the surface of the pipeline, and use a steel brush to remove the surface oxide scale. Place the treated workpiece in the electrolytic cell with the workpiece to be treated as the anode and graphite as the cathode. 2 The electrolysis was carried out for 100 s. The electrolyte consisted of NiCl2·6H2O, HCl and NaCl.

[0063] 2) Slurry coating on pipeline surface

[0064] After preheating the pipe at 220℃ for 30 minutes, apply the slurry to a suitable thickness at one time by spraying (or brushing, etc.), and do not apply it in layers multiple times; the thickness of the coating slurry layer is 0.8mm.

[0065] The preparation method of the metal powder coating raw material is as follows: according to the mass percentage of the solid phase components, 70% of chromium powder, 5% of nickel powder, 3% of iron, 2% of aluminum powder and 20% of lanthanum oxide are weighed respectively, and the mixed metal mixed powder is ball-milled at a ball milling speed of 350 to 400 r / min and a ball milling time of 6 to 24 hours to obtain the final solid phase components.

[0066] The liquid phase component is measured by mass percentage, and 10% Al (H2PO4), 5% water glass, 5% ammonium bromide, 20% acrylic resin, 30% epoxy resin and 30% curing agent are mixed and stirred to obtain the liquid phase component. The solid phase component and the liquid phase component are mixed according to the solid-liquid (g: ml) ratio of 10:1 to 5 to obtain the final metal powder coating raw material.

[0067] 3) Drying and curing

[0068] The metal pipe coated with the chromizing material was pre-dried at 60°C for 5 minutes, then dried at 100°C for 55 minutes, and finally cured at 250°C for 30 minutes.

[0069] 4) Rapid sintering

[0070] The pipeline is rapidly sintered, diffused and chromized by rapid heating, and then air-cooled to room temperature; the heating rate is set to 1000°C / min, the holding temperature is 1100°C, and the holding time is 30min.

[0071] Example 5

[0072] The difference from Example 4 is that the liquid phase components are measured by mass percentage, including 25% Al(H2PO4), 10% water glass, 7% ammonium bromide, 20% acrylic resin, 18% epoxy resin and 20% curing agent.

[0073] Grind the prepared coal ash thoroughly and add appropriate amount of acetone to make a suspension, and evenly coat it on the surface of the chromium-nickel cladding coating sample prepared in Examples 1 to 5, with a coating amount of about 50 mg / cm2. Place the sample in a constant temperature tubular heating furnace and heat it to 750°C. Continue to introduce mixed flue gas into the tubular furnace with a flue gas flow rate of 100 mL / min. Use a honeycomb Pt mesh as a catalyst to convert SO2 into SO3. Use a saturated NaOH solution to neutralize the remaining SO2 in the tail gas at the outlet of the tubular furnace. When the corrosion test is carried out for 50h, 200h, 300h and 500h, take out the sample, remove the residual coal ash on the surface, and weigh it after cleaning and drying. The mass change (mg / cm 2 ) as shown in Table 1.

[0074] Table 1 Mass change of the chromium-nickel co-penetration coating prepared in Examples 1 to 5 in 750°C coal ash / flue gas (mg / cm 2 )

[0075]

[0076] Figure 1 This is a cross-sectional morphology of the chromium-rich high-temperature corrosion-resistant coating prepared on the surface of austenitic steel in Example 1 of the present invention. Figure 2 The cross-sectional morphology of the chromium-rich high-temperature corrosion-resistant coating prepared on the surface of austenitic steel in Example 5 of the present invention. The chromium-nickel cladding coating prepared in Example 1, in a 750°C coal ash / smoke environment, has poor stability of the oxide film after the corrosion time exceeds 300h, and begins to lose weight, and the oxide film peels off in large quantities; the corrosion rate of the chromized coating prepared in Examples 2 and 3 gradually accelerates after the corrosion time exceeds 200h, and the corrosion rates are 0.0119mg / (cm 2 ·h) and 0.0139mg / (cm 2 ·h), the corrosion resistance of the coating is poor; the weight gain trend of the chromium-nickel corrosion-resistant coating prepared in Example 4 within 500h conforms to the linear law, and the corrosion rate of the coating in a 750℃ coal ash / flue gas environment is basically stable; the weight gain trend of the coating prepared in Example 5 conforms to the parabolic law, and the coating has good corrosion resistance in a 650℃ coal ash / flue gas environment.

[0077] The hardness of the base material and the coatings prepared in Examples 1 to 5 were measured using a HV-1000A microhardness tester. The test load was selected as 200g, the holding time was 10s, and 6 points at different horizontal positions were selected for testing, and the average value was taken. The hardness of the austenitic steel base material is 250HV 0.2 The microhardness of the coatings prepared in Examples 1 to 5 is 269 HV 0.2 、281HV 0.2 、303HV 0.2 、328HV 0.2 and 403HV 0.2 , indicating that the chromium-nickel co-diffusion coating prepared in the present invention can strengthen the matrix structure and improve the hardness and wear resistance of the tube wall surface.

[0078] Comparative Example 1

[0079] The difference between this comparative example and Example 5 is that the liquid phase components are replaced by: 25% Al(H2PO4)3, 10% water glass, 7% ammonium bromide, 38% acrylic resin, and 20% curing agent.

[0080] Comparative Example 2

[0081] The difference between this comparative example and Example 5 is that the liquid phase components are replaced by: 25% Al(H2PO4)3, 10% water glass, 7% ammonium bromide, 38% epoxy resin, and 20% curing agent.

[0082] Comparative Example 3

[0083] The difference between this comparative example and Example 5 is that the liquid phase components are replaced by: 25% Al(H2PO4)3, 10% water glass, 7% ammonium bromide, 38% vinyl ester, and 20% curing agent.

[0084] Comparative Example 4

[0085] The difference between this comparative example and Example 5 is that the solid phase components are replaced by: 70% chromium powder, 5% nickel powder and 25% lanthanum oxide.

[0086] Comparative Example 5

[0087] The difference between this comparative example and Example 5 is that the solid phase components are replaced by: 80% chromium powder, 15% nickel powder, 3% iron and 2% aluminum powder.

[0088] Comparative Example 6

[0089] The difference between this comparative example and Example 5 is that the pretreatment process of the workpiece in step (1) is changed to using alcohol / acetone to clean the oil stains, dust, etc. on the surface of the pipeline, and the surface oxide scale is removed by a steel brush, and then the pipeline is directly preheated at 220°C for 30 minutes without activation.

[0090] The corrosion resistance of the chromium-nickel cladding coating samples prepared in Example 5 and Comparative Examples 1 to 6 in coal ash / smoke at 750°C was tested. The mass change (mg / cm 2 ) as shown in Table 2.

[0091] Table 2 Mass changes of the chromium-nickel co-penetration coatings prepared in Example 5 and Comparative Examples 1 to 6 in 750°C coal ash / flue gas (mg / cm 2 )

[0092]

[0093] According to the standard requirements of GB / T 31541-2015 "Test Method for Tensile and Shear Bond Strength of Fine Ceramics Interface Cross Method", the bond strength of the adhesive samples prepared in Example 5 and Comparative Examples 1 to 3 was tested respectively. The bond strength between the adhesive sample corresponding to Example 5 and the metal substrate was greater than 10MPa, the bond strength of the adhesive samples corresponding to Comparative Examples 1 and 2 was greater than 8MPa and less than 10MPa, and the bond strength of the adhesive sample corresponding to Comparative Example 3 was less than 6MPa. Acrylic resin can improve the bond strength of aluminum dihydrogen phosphate adhesive, and when used for modification together with epoxy resin, the effect of enhancing the bond strength is better. In a 750°C coal ash / flue gas environment, the coating prepared in Comparative Example 3 has poor stability of the oxide film after the corrosion time exceeds 300 hours, begins to lose weight, and the oxide film peels off in large quantities; the corrosion rate of the chromium-nickel cladding coatings prepared in Comparative Examples 1 and 2 gradually accelerates after the corrosion time exceeds 200 hours; in summary, the multi-component composite binder used in the present invention can increase the concentration of chromium and nickel atoms on the outside of the tube wall by increasing the adhesion strength between the coating layer and the substrate, thereby improving the high and low temperature corrosion resistance and steam oxidation resistance of the carburized layer and extending the service life of the carburized layer.

[0094] After the corrosion time of the chromium-nickel cladding coating prepared in Comparative Example 6 exceeds 200 hours, the corrosion rate gradually accelerates and the corrosion resistance of the coating is poor, indicating that the electrolytic activation process can make the surface of the metal to be infiltrated in an "activated" state, increase the speed at which chromium and nickel atoms penetrate into the matrix, and thus improve the corrosion resistance of the coating.

[0095] The metal powder infiltrated chromium-nickel high-temperature corrosion-resistant coating and its preparation method described in the present invention do not need to be carried out under vacuum conditions, and the preparation process is simple. At the same time, the chromium-nickel infiltrated layer has high preparation efficiency, low pollution, adjustable thickness, good wear resistance, and especially excellent resistance to high and low temperature corrosion and steam oxidation.

[0096] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. A method for preparing a chromium-nickel co-penetration coating by a slurry method using a liquid phase multi-component composite binder, characterized in that: The method comprises the steps of cleaning the workpiece, electrolytically activating the workpiece and then preheating the workpiece, applying a chromium-nickel metal slurry coating to the surface of the workpiece, drying and curing the workpiece in stages, and finally rapidly sintering the workpiece, wherein the chromium-nickel metal slurry coating comprises a solid phase component and a liquid phase component.

2. The preparation method according to claim 1, characterized in that: The solid phase components include, by mass percentage, 50-80% of chromium powder, 0-10% of nickel powder, 2-20% of iron, 0-5% of aluminum powder and 0-45% of lanthanum oxide.

3. The preparation method according to claim 1, characterized in that: The liquid phase components include, by mass percentage, 10-30% Al(H2PO4)3, 5-15% water glass, 5-10% ammonium bromide, 10-30% acrylic resin, 10-30% epoxy resin and 10-30% curing agent.

4. The preparation method according to claim 1, characterized in that: The workpieces include, but are not limited to, carbon steel, austenitic stainless steel, and high temperature alloys.

5. The preparation method according to claim 1, characterized in that: The preheating temperature is 150-220° C. and the preheating time is 30-60 minutes.

6. The preparation method according to claim 3, characterized in that: The solid phase component and the liquid phase component are mixed at a solid-liquid (g:ml) ratio of 10:1 to 5.

7. The preparation method according to claim 2, characterized in that: The solid phase component is ground at a speed of 350 to 400 r / min for 6 to 24 hours.

8. The preparation method according to claim 1, characterized in that: The staged drying and curing comprises pre-drying at 75-85° C. for 5-30 minutes, drying at 140-160° C. for 30-60 minutes, and finally medium-temperature curing at 250-300° C. for 30-60 minutes.

9. The preparation method according to claim 1, characterized in that: The sintering temperature is 900-1150° C. and the sintering time is 5-30 minutes.

10. The chromium-nickel co-penetration coating obtained by the preparation method according to claims 1 to 9.

Citation Information

Patent Citations

  • Aerogel core material capsule, paint prepared from same and preparation method of paint

    CN105363396A

  • High-temperature resistance environment-friendly insulating coating for electrical steel and preparation method of high-temperature resistance environment-friendly insulating coating

    CN109266140A

  • Preparation method of chromium-enriched high-temperature corrosion resisting coating deposited through slurry method

    CN109881145A

  • Thermophilic corrosion-resistance coating

    CN1121538A

  • Laser cladding method based on alloying layer

    CN116121747A